(untitled) (Research, Society and Development, 2022)
Attention Deficit Hyperactivity Disorder is a complex disorder that has a controversial diagnosis. The first theory, biomedical, considers neurobiology and the second, historical-social psychology and delimits itself in this field of reasoning to understand the disorder and its commitments. The prevalent symptoms are impulsivity, inattention and hyperactivity, and the disorder is widely studied in an interdisciplinary manner. Among the many consequences and consequences of ADHD, the psychic functions are the most compromised part and from them, the potential damages for schooling, learning, relationships and social interactions. The present study is justified by the need to better explore the theme and aims to analyze the impairments at psychic levels, highlighting the two conceptual strands for ADHD. To this end, we used a bibliographic research, of a descriptive and exploratory nature, regarding the objectives. The resulting textual production comprises, in three topics, the results obtained and the discussions allowed, respecting the conceptual limits of each theoretical aspect. The impressions and conclusions are described in the Final Considerations.